Influence of Magnetic Repulsion on Vibration Energy Harvesting - Nehal El-Bedwehy; Mogeeb El-Sheikh; Abla El-Megharbel; Mustafa Arafa (Port Said Engineering Research Journal, 2018)
The progress in electronic devices, including the wireless sensors, leads to the great demand on powering these devices which utilize wireless sensor systems. Recent researches focused on nonlinear energy harvesters to overcome the limitations of linearity. Magnets are a common method that used to achieve nonlinearity to the system. In this paper the effect of nonlinear magnetic force on the response of the energy harvester proposed. A model of a cantilever beam with tip magnet opposing a fixed magnet is introduced. The mathematical model predicted the response of the cantilever beam with and without the magnet effect. By changing the gap distance between the magnets, the response of the harvester investigated. Experimental work carried out to validate the results of the mathematical approach. The mathematical model shows a good agreement with experimental model results for different gap values. The results prove that repelling magnetic force leads resonance frequency to a larger value. Tip displacement of cantilever beam changed according to gap distance (d). Without magnet, the cantilever moves freely without magnetic force constraint so maximum displacement reaches about 17 mm. In another hand, maximum tip displacement decreases by decreasing the gap distance as the magnetic force restricts free motion of the beam.